2021
DOI: 10.21315/tlsr2021.32.2.3
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory Effects of Asiaticoside Against Shigella flexneri-Infected Macrophages

Abstract: Macrophages provide the first line of defense against Shigella flexneri infection in the gastrointestinal tract by inducing a variety of inflammatory and antimicrobial responses. Secondary metabolites of plants are used as drugs against infections that are resistant to common antibiotics. In this study, the innate effects of asiaticoside on the proinflammatory activity of mouse macrophages infected with S. flexneri were investigated. The viability of the infected mouse macrophages were examined using viability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…The earlier reports have established ASA as a neuroprotective agent that can cross the blood–brain barrier (Hanapi et al 2021 ). Further, Michael et al ( 2021 ) have shown the immunomodulatory activity of macrophages infected with S. flexneri , and have also noted the improvement in the killing action of macrophages. In our findings, the ASA is a potent antibacterial compound that gave 90% growth inhibition ( Table 2 ) on extensively drug-resistant tubercle bacilli and 100% on reference strain E. coli .…”
Section: Resultsmentioning
confidence: 95%
“…The earlier reports have established ASA as a neuroprotective agent that can cross the blood–brain barrier (Hanapi et al 2021 ). Further, Michael et al ( 2021 ) have shown the immunomodulatory activity of macrophages infected with S. flexneri , and have also noted the improvement in the killing action of macrophages. In our findings, the ASA is a potent antibacterial compound that gave 90% growth inhibition ( Table 2 ) on extensively drug-resistant tubercle bacilli and 100% on reference strain E. coli .…”
Section: Resultsmentioning
confidence: 95%
“…Consequently, Chinese herbs and their extracts have emerged as a potential alternative [ 10 ]. Asiaticoside (Asi), the main glycosidic compound extracted from Centella asiatica (L.) Urban , is well known for its cosmetic effects, anti-inflammatory properties, and promoting wound healing [ 11 , 12 , 13 ]. Moreover, Asi has been shown to have an anti-diabetic effect in a high-fructose-fat-fed rat model [ 14 ].…”
Section: Introductionmentioning
confidence: 99%